Bacteriological Spectrum of Pediatric Urinary Tract Infection and Its Drug Sensitivity and Resistance Pattern - Nadia Mumtaz, Qaiser Shehzad Humayoun, Israr Liaquat, Tariq Mahmood, Muhammad Hafeez, Hifza Zeb (Journal of Rawalpindi Medical College, 2022)
Introduction: - Urinary tract infection (UTI) is common infection in children. It has high morbidity and long term sequelae. Objective: To determine the frequency of bacteriological organism of Pediatric UTI and its drug sensitivity and resistance pattern and to improve the treatment of UTI according to culture sensitivity, hence to minimize the resistance pattern and disease burden. Material and methods: It was a descriptive cross sectional study conducted during 2018 over a period of 6 months. Total 225 children with UTI were enrolled. Urine culture and sensitivity reports were evaluated and an isolated microorganism along with their sensitivities to the mentioned drugs was entered through designed Performa. Results: - The average age of the children was 7±.18 years. Common bacteriological agents leading to UTI was E.Coli (59.1%), followed by Pseudomonas aeruginosa (14.2%), klebsiella (13.8%) , stapylococcus aureus (8.9%) and enterococcus (4%). Most common organism isolated was E.coli ( 133 cultures). It was fully resistant with amoxicillin clavulanate and ofloxacin (100%), while resistant pattern with other antibiotics, ceftriaxone (88.7%), imipenam (88.7%), ciprofloxacin (75.9%). the most effective antibiotic for E.coli was amikacin (81.2%). klebisella was isolated in 31 cultures. Conclusion: Most common organism that cause UTI was E.coli followed by Pseudomonas Aeroginosa and Klebsiella. These isolates were highly resistant to commonly used antibiotics. Therefore new antibiotics policy should be adopted to treat these infections.